(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
The dynamic lifestyle, altered value models of behavior in people, mobility of the population, hedonistic way of life and the liberal view of divorce, result in the realization of personal needs and interests, before those of the family, which undoubtedly affect the galloping number of divorces in the past few decades. Divorce as a social phenomenon that exists in many cultures around the world, a state in which no society and state is immune to its occurrence. The divorce is an important topic for analyzing from aspect of the consequences, as well as the occurrence of changes in the family system. The legal regulation of divorce is closely related to the historical, moral, economic, cultural and religious circumstances that were dominant in certain periods of their history of their history. In this paper we will consider and study the various systems of divorce in the world as well as in the Republic of North Macedonia in order to draw appropriate conclusions and recommendations for further research.